Elphinstone building - Ghosh, Ayan (2023)
Located at the intersection of Veer Nariman Marg and SA Brelvi Road, Elphinstone Building was designed by Rienzi Giesman Walton (1842-1900). As a municipal engineer, Walton executed several landmark projects in Mumbai, notably the Elphinstone Circle Garden, Northbrook Garden, Hanging Gardens at Malabar Hill, and Colaba Market, among many others.